2014
DOI: 10.1530/joe-14-0461
|View full text |Cite
|
Sign up to set email alerts
|

ANIMAL MODELS OF DISEASE: Feline hyperthyroidism: an animal model for toxic nodular goiter

Abstract: Since first discovered just 35 years ago, the incidence of spontaneous feline hyperthyroidism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 153 publications
(227 reference statements)
3
66
0
Order By: Relevance
“…While this was successful, our results also suggest cats may have individual set points for thyroid function similar to humans as it has been documented that individuals have different set points which result in unique thyroid functions (Andersen, Pedersen, Bruun, & Laurberg, ). There has been recent interest in using cats as an animal model for human thyroid research, particularly for toxic multinodular goitre as the subclinical, clinical and histological progression of the human disease is nearly identical to feline hyperthyroidism (Peterson, ; Wakeling et al., ), and our results also provide further support that cats may be an excellent animal model for thyroid diseases.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…While this was successful, our results also suggest cats may have individual set points for thyroid function similar to humans as it has been documented that individuals have different set points which result in unique thyroid functions (Andersen, Pedersen, Bruun, & Laurberg, ). There has been recent interest in using cats as an animal model for human thyroid research, particularly for toxic multinodular goitre as the subclinical, clinical and histological progression of the human disease is nearly identical to feline hyperthyroidism (Peterson, ; Wakeling et al., ), and our results also provide further support that cats may be an excellent animal model for thyroid diseases.…”
Section: Discussionsupporting
confidence: 70%
“…It is suspected that cats have a long subclinical state of hyperthyroidism, before developing overt hyperthyroidism (Wakeling et al., ). During this subclinical state, TT4 and TT3 will be within the normal range while TSH will be low or undetectable (Peterson, ; Wakeling et al., ). However, due to the lack of available feline specific TSH assays (Peterson et al., ), laboratories use canine TSH assays as feline TSH has 96% homology to canine TSH (Rayalam, Eizenstat, Hoenig, & Ferguson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Since idiopathic hypertension occurs in the minority of hypertensive cats (Jepsen, 2011), it was considered unlikely and consequently ruled out. Hyperthyroidism was excluded because there was no clinical suspicion and no thyroid lesions were identified by gross and histopathological examination (Peterson, 2012). Finally, acromegaly was ruled out because there was no clinical suspicion and no skeletal abnormalities and pituitary adenomas were detected at post mortem examination (Greco, 2012).…”
Section: Animalsmentioning
confidence: 99%
“…Rather, these calculations are generally based on an estimation of thyroid volume, thyroid 131 I uptake, and 131 I retention time within the thyroid gland . In human patients with toxic nodular goiter (most similar to the feline disease), investigators have reported the usefulness of adding TcTU measurements to the 131 I dose protocols to increase efficacy of treatment . In addition, TcTU may also play a prognostic factor for predicting 131 I treatment outcome (i.e., euthyroid, hypothyroid, persistent hyperthyroidism); in one study, the finding of high TcTU was predictive for treatment failure when a fixed dose 131 I method was used .…”
Section: Discussionmentioning
confidence: 99%
“…However, since quantitative scintigraphy also provides insight into the overall functional and metabolic activity of the gland, this information could potentially be used to help determine the optimal radioiodine ( 131 I) dose for effective treatment and predict the response to 131 I treatment. In humans with toxic nodular goiter (type of hyperthyroidism most similar to the feline disease), scintigraphic characteristics such as the percent thyroid uptake, heterogeneous distribution of radionuclide uptake, and thyroid size or volume are used to aid radioiodine‐dosing schemes. Although T/S or T/B ratios have sometimes been used in human patients to aid in diagnosis, they have not been reported as part of any radioiodine dosing calculations used in human patients with toxic nodular goiter.…”
Section: Introductionmentioning
confidence: 99%